Morinda citrifolia Linn. Ethanolic-extract Improve Inflammation Condition in Acetic Acid-induced Colitis Ulcerative Mice Models - Utami, Tri Fitri Yana; Sahid, Muhammad Novrizal Abdi; Sari, Ika Puspita; Sasmito, Ediati (Majalah Obat Tradisional, 2025)
Ulcerative Colitis (UC) is a chronic inflammatory disorder affecting the colon, characterized by recurrent episodes and involving multifaceted etiological factors in its pathogenesis. This study aims to explore the pharmacological effect of Morinda citrifolia Linn. fruit ethanolic-extract (MFE) in UC. The UC mice model was induced using 2% acetic acid administered per-rectal. Subsequently, mice were categorized into six groups, comprising a normal control, negative control, positive control, and three MFE treatment groups (100mg/kgBW; 200mg/kgBW; 400mg/kgBW). Colitis severity was assessed by scoring system to obtain the Disease Activity Index (DAI) and Hematoxylin-Eosin (HE) staining. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was employed to determine the free radical scavenging activity. MFE exhibited notable antioxidant activity, with an IC50 value of 0,553 mg/ml. Notably, MFE administration led to a discernible reduction in DAI scores, with MFE treatment demonstrating improved inflammation condition compared to the negative control from day 6 through day 11. Furthermore, immune cell infiltration within colonic tissue was markedly attenuated in the MFE-treated group compared to the negative control group. Evaluation of colon tissue damage revealed scores of 5.7, 4.2, and 3 for MFE doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg, respectively, whereas the positive control group exhibited a score of 3, indicating superior tissue preservation. Notably, these scores contrasted starkly with the negative control group, which registered a damage score of 11.8. These findings exhibit the MFE potential as a therapeutic intervention for UC owing to its pharmacological properties, underscoring its potential as a natural remedy in UC management.